Perancangan bangunan pelindung pantai dalam penanganan abrasi (studi kasus: Pantai Caruban, Jawa Tengah) - M Gilang Indra Mardika; Tera Melya Patrice Sihombing; Retno Hutami Adinigsih (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Citing from the National Disaster Management Agency (BNPB) in 2022, abrasion occurred located at Caruban Beach, Gedongmulyo Village, Lasem District, Rembang Regency, Central Java Province. The impact of this abrasion causes a significant change in the coastline. One of the efforts to overcome these problems is to plan coastal protection which is adjusted to the existence of the parameters and urgency on Caruban Beach. The main aims of this research is planning breakwater structure as coastal protection and addressing the abrasion. The parameters used in the planning of coastal protection include significant wave height, tides with HHWL values, refractive coefficients, and shoaling coefficients for the transformation of deep water into shallow water, the raise up of water surface, and Sea Level Rise value. The data on high and significant wave periods are processed using the probability distribution of the Fisher Tippett Type I method at a 50-year return period with high values and extreme wave periods of 2.402 meters and 5.61 seconds, respectively. Waves transformation by the refractive coefficient and shoaling coefficient is derived around 1.57 meters at a depth of 5 meters. HHWL value is earned at 0.928 meters. The value of wave set-up is 0.11 meters, while sea level rise in the best estimate in 2075 is 0.24 meters. So design water level is 1.28 meters. The coastal protection chosen is offshore breakwater because it serves to maintain the position of the coastline and maintain the function of Caruban Beach as tourist destination. Breakwater planning uses three types of protective layers, namely tetrapods, dolos, and boulders, where the wave propagation value on the three types of protective layers is derived consecutively of 0.73 meters, 0.68 meters, and 1.46 meters. Thus, the elevation of the tetrapod, dolos, and boulder protection layers is 2.6 meters respectively, 2.5 meters, and 3.3 meters.